A moldura em análise - Bessa, Juliana Cristina [UNESP]; Teixeira Filho, Fernando Silva [UNESP]; Santos, Kwame Yonatan P. [UNESP]; Costantin, Juliana Rezende [UNESP]; Lima, Juliana Lopes [UNESP]; Silva, Thyfani Domingues da [UNESP] (My University, 2011)
Considering that our practice is intended to deconstruct stigmas andstereotypes socially produced and institutionalized from normativities ofgender and sexuality, this work proposes a reflection on two issues which hascaused concerns: the secrecy and the ethics in relation to the patients whocome to us. This is because, most of these are LGBTs (lesbian, gay, bisexual,transvestite, transsexual and transgender), and that by being in a situation ofghettoization created by homophobia and resized by inner city context, aresubject to coexist and to relate, what makes be serviced by the same internshipproject or have friends or lovers in this. And, in this configuration, the group isquestioned by ethical dilemmas which imposes on the therapeutic relationship,forcing him to repositioning the respect of aesthetics, this is, the pictureframe setting, the treatment policy, the transference, the ethics and thesecrecy, forcing these concepts to the limit.

Considerando que nossa prática tem o intuito de desconstruir estigmas e estereótipos socialmente produzidos e institucionalizados a partir das normatividades de gênero e sexualidade, este trabalho propõe uma reflexão em torno de duas questões que nos tem causado inquietações: o sigilo e a ética relativamente ao atendimento dos pacientes que nos procuram. Isto porque, a maioria dentre estes são LGBTs (lésbica, gay, bissexual, travesti, transexual e transgênero), e que por estarem em situação de “guetificação” criada pela homofobia e redimensionada pelo contexto de cidade do interior, estão sujeitos a conviver e a se relacionar, o que facilita serem atendidos pelo mesmo projeto de estágio ou terem amigos/as ou namorados/as neste. E é nessa configuração, que o grupo encontra-se interpelado por dilemas éticos que se impõe à relação terapêutica, forçando-o a se reposicionar a respeito da estética, isto é, da “moldura” – setting; da política do tratamento, ou seja, da transferência; e da ética e do sigilo, forçando estes conceitos ao limite.
The setting in analysis
Keywords: Ethics; Secrecy; Psychological clinic; LGBT; Sexual diversity; Ética; Sigilo; Clínica psicológica; LGBT; Diversidade sexual